Identifikasi Zat Warna Rhodamin B Pada Lipstik Yang Beredar Di Pasar Kota Palu - Purniati, Ni Ketut; Ratman, Ratman; Jura, Minarni Rama (Jurnal Akademika Kimia, 2015)
Rhodamine B is a synthetic dye used for colouring of paper, textiles and inks. Rhodamine B is able to cause an irritation of the respiratory tract, liver damage and as a carcinogenic substance. The use of dyes aims to obtain more attractive colour. This study aims to identify the rhodamine B on lipsticks in the market in Palu City. The dye was determined using thin layer chromatography (TLC) through qualitative and quantitative tests. The results showed that all lipstick samples were negative containing rhodamine B. Based on qualitative test by TLC did not found similar Rf 0.72 cm confirming the reference solution for rhodamine B, where the value of Rf on consecutive samples were 1A code samples obtained value Rf = 0.58 cm, the sample code 2A obtained value Rf = 0.46 cm, the sample code 3A Rf value = 0.68 cm, the sample code 4A obtained Rf = 0.65 cm, code samples obtained 1B Rf = 0.49 cm, and the sample code 2B obtained value Rf = 0.50 cm. Based on this study it can be concluded that all 6 lipstick samples tested did not contain rhodamine B.